Efficacy of palliative radiation therapy for symptomatic rectal cancer. Issue 2 (November 2016) - Chia, David; Lu, Jiade; Zheng, HuiLi; Loy, EnYun; Lim, Keith; Leong, ChengNang; Wong, LeaChoung; Tan, Gabriel; Chen, Desiree; Ho, Francis; Tey, Jeremy
Abstract: 99 patients with symptomatic locally advanced rectal cancer who were treated with palliative radiation alone were reviewed. Dose-fractionation ranged from 18 to 54 Gy. Response rate ranged from 62.5 to 86.7%, with a median response duration ranging 4.2–5.4 months. Median survival was 6.9 months. Using a BED cut-off of 39Gy10, no dose–response relationship was found.